Kasabach-Merritt Phenomenon: Diagnosis, Management, and Outcome on Two Cases in a Sub-Saharan Country (Senegal) - Diop, Khadim; Ndiaye Diop, Mame Téné; Diop, Ibrahima; Mejri, Ines; Yassine, Lana; Diassé, Fatou; Tall, Fatime; Ba, Idrissa Demba; Ndiaye, Maodo; Ndiaye, Ousmane (Case reports in dermatology, 2025)
Introduction: Kasabach-Merritt phenomenon (KMP) is a rare and life-threatening disease, characterized by the profound thrombocytopenia and consumptive coagulopathy associated with vascular tumors. In sub-Saharan Africa, KMP-related data are scarce and it poses significant challenges in management, particularly due to limited availability of treatment resources. We report 2 cases of KMP observed in a sub-Saharan Africa country (Dakar, Senegal). Case Presentation: Case 1: a 45-day-old male infant was admitted for a tumor lesion located in the axillary fold that has been evolving since birth. The lesion had rapidly become aggressive, inflammatory, and purpuric. Blood tests showed normocytic normochromic anemia with severe thrombocytopenia and high D-dimer levels. The diagnosis of a kaposiform hemangioendothelioma complicated by a KMP was retained. Treatment with betamethasone was initiated, but death occurred 6 days later secondary to cerebral hemorrhage. Case 2: a 2-month-old female infant was admitted for a rapidly aggressive, inflammatory, infiltrating tumor lesion on the face that had been progressing for 1 month. Blood tests showed normocytic normochromic anemia with severe thrombocytopenia and high D-dimer levels. The diagnosis of a KMP was retained. Treatment with corticosteroids, then combined with vincristine, was administered. The outcome was favorable with a considerable regression of the mass and improvement in biological parameters after 6 months. Conclusion: To our knowledge, we report the first case report on KMP in sub-Saharan Africa, particularly in pediatric dermatology in Dakar. Besides their rarity, these cases highlight the challenges in the management of KMP in a country with limited therapeutic resources.